Biological control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Biological control by Roy G van Driesche and Thomas S. Bellows, Jr 1996 539pp price UKL55 00 ISBN 0 412 02861 1